2021
DOI: 10.1186/s12903-021-01871-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between psychological wellbeing, depression, general anxiety, perceived social support, tooth brushing frequency and oral ulcers among adults resident in Nigeria during the first wave of the COVID-19 pandemic

Abstract: Introduction The aims of this study were to determine the associations between psychological wellbeing, and the frequency of tooth brushing and presence of oral ulcers during the COVID-19 pandemic; and to identify the mediating roles of psychological distress (general anxiety and depression) and perceived social support in the paths of observed associations. Methods This cross-sectional study recruited 996 adults in Nigeria between June and August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…Comparing the results of the studies using validated and non-validated questionnaires, there were differences in the percentage of dentists suffering from anxiety, with higher frequencies in those studies carried out with non-validated questionnaires (ranging from 7.1 to 71% with validated questionnaires [ 71 , 83 ] vs. 25.6 to 89% with non-validated questionnaires [ 64 , 81 ]). This was also observed in the studies that analysed adult patients under general treatment (ranging from 4.5 to 5.1% with validated questionnaires [ 100 , 108 ] vs. 9.5 to 62.4% with non-validated questionnaires [ 76 , 133 ]). Similarly, studies analyzing the percentage of patients presenting fear reported higher values with validated questionnaires (from 45 to 45.7% [ 100 , 120 ]) than with the non-validated ones (62.4 to 63.6% [ 115 , 133 ]).…”
Section: Resultssupporting
confidence: 63%
“…Comparing the results of the studies using validated and non-validated questionnaires, there were differences in the percentage of dentists suffering from anxiety, with higher frequencies in those studies carried out with non-validated questionnaires (ranging from 7.1 to 71% with validated questionnaires [ 71 , 83 ] vs. 25.6 to 89% with non-validated questionnaires [ 64 , 81 ]). This was also observed in the studies that analysed adult patients under general treatment (ranging from 4.5 to 5.1% with validated questionnaires [ 100 , 108 ] vs. 9.5 to 62.4% with non-validated questionnaires [ 76 , 133 ]). Similarly, studies analyzing the percentage of patients presenting fear reported higher values with validated questionnaires (from 45 to 45.7% [ 100 , 120 ]) than with the non-validated ones (62.4 to 63.6% [ 115 , 133 ]).…”
Section: Resultssupporting
confidence: 63%
“…Prior studies indicated that aphthous, hemorrhagic, and necrotic oral ulcers were associated with COVID-19 [ 71 , 72 ]. Previous studies also suggested that the pandemic is associated with a higher risk of reduced tooth brushing frequency [ 15 , 73 , 74 ]. This raises concern over the long-term impact of the pandemic on people at risk of periodontal-induced health risks [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of tooth brushing is lower in people dealing with psychological distress [ 12 ], such as depression [ 13 ] and suicidal ideation [ 14 ], and psychological well-being during a crisis like the COVID-19 pandemic is associated with a decrease in tooth brushing frequency [ 15 ]. Psychological distress can be caused by emotional stress like loneliness [ 16 ], dental anxiety [ 17 ], frustration or boredom [ 18 ], anger [ 19 ], grief, or feeling of loss [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 On the other hand, Folayan et al reported that in the COVID-19 pandemic, one tenth of the adult individuals evaluated reported having reduced the regularity with which they brushed their teeth; likewise, the interruption of this healthy habit would be linked to the development of disorders such as anxiety and decreased psychological well-being. 17 From the aforementioned, it can be derived that the modification of such an important daily routine due to such complex scenarios as a health emergency would influence the deterioration of oral hygiene maintenance.…”
Section: Discussionmentioning
confidence: 99%